Brain bioenergetics in rats with acute hyperphenylalaninemia. (July 2018) - Dimer, Nádia Weber; Ferreira, Bruna Klippel; Agostini, Jotele Fontana; Gomes, Maria Luiza; Kist, Luiza Wilges; Malgarin, Fernanda; Carvalho-Silva, Milena; Gomes, Lara Mezari; Rebelo, Joyce; Frederico, Marisa Jádna Silva; Silva, Fátima Regina Mena Barreto; Rico, Eduardo Pacheco; et al.
Abstract: Phenylketonuria (PKU) is a disorder of phenylalanine (Phe) metabolism caused by deficient phenylalanine hydroxylase (PAH) activity. The deficiency results in increased levels of Phe and its metabolites in fluids and tissues of patients. PKU patients present neurological signs and symptoms including hypomyelination and intellectual deficit. This study assessed brain bioenergetics at 1 h after acute Phe administration to induce hyperphenylalaninemia (HPA) in rats. Wistar rats were randomized in two groups: HPA animals received a single subcutaneous administration of Phe (5.2 μmol/g) plus p-Cl-Phe (PAH inhibitor) (0.9 μmol/g); control animals received a single injection of 0.9% NaCl. In cerebral cortex, HPA group showed lower mitochondrial mass, lower glycogen levels, as well as lower activities of complexes I-III and IV, ATP synthase and citrate synthase. Higher levels of free Pi and phospho-AMPK, and higher activities of LDH, α-ketoglutarate dehydrogenase and isocitrate dehydrogenase were also reported in cerebral cortex of HPA animals. In striatum, HPA animals had higher LDH (pyruvate to lactate) and isocitrate dehydrogenase activities, and lower activities of α-ketoglutarate dehydrogenase and complex IV, as well as lower phospho-AMPK immunocontent. In hippocampus, HPA rats had higher mRNA expression for MFN1 and higher activities of α-ketoglutarate dehydrogenase and isocitrate dehydrogenase, but decreased activities of pyruvate dehydrogenase and complexes I and IV. In conclusion, our data demonstrated impaired bioenergetics in cerebral cortex, striatum and hippocampus of HPA rats. Highlights: Hyperphenylalaninemia (HPA) and intellectual disability are found in phenylketonuria. HPA increases serum lactate levels, decreases glycogen content in brain and activates AMPK. HPA alters mitochondrial enzyme activities in brain. HPA alters mitochondrial dynamics. Brain bioenergetics may be involved in the neurological damage presented by patients affected by phenylketonuria.